Organizational innovation capability as a result of knowledge management processes - a literature review - Inków Monika (Management, 2020)
Nowadays, innovation and innovativeness have become a key conditioning factor in the survival of an organization. The organizations should have a sufficiently high level of innovation capability to be able to effectively develop and implement new solutions. Currently, researchers are increasingly talking about knowledge management processes in the context of creating and developing innovation capability of an organization (e.g. Hussein et al. 2016; Wijekoon and Galahitiyawe 2016). As noted by Hussein et al. (2016), sharing knowledge in a dynamically changing business environment is gaining key importance for the success of an organization. Knowledge itself, on the other hand, is indicated as a key source of innovation in the literature on knowledge management (Wijekoon and Galahitiyawe 2016; Monferrer et al. 2014; Nonaka et al. 2000; Yesil et al. 2013).